Chronisch-entzündliche Darmerkrankungen: Diagnostik und Therapie in der Praxis - Teich, Niels; Klugmann, Tobias (DMW - Deutsche Medizinische Wochenschrift, 2018)
Significant increases in Crohn’s disease incidence have been noticed in recent decades. Therefore it gets more important to increase practical knowledge, present therapy innovations and draw attention to the need for vaccinations of immunosuppressed IBD patients as well as useful supportive therapy options.
Keywords: Morbus Crohn; Colitis ulcerosa; Azathioprin; Impfung; Eisenmangel